Children of the Eagle - Adimora-Ezeigbo, Akachi (Literamed Publications Ltd, 2002)
This novel is the third and last part of the Umuga trilogy- a saga based on the history of my community, a town in Eastern Nigeria. The Saga explores the lives of men and women of four generations of two families and some other important and unimportant characters who lived in the same period and whose lives impacted on one another. The first and second parts of the trilogy- The Last of the Strong ones and House of Symbols are connected.
Keywords: Fiction